The use of innovative tools of territory marketing - Galina Vladimirovna Vorontsova; Natalya Evgen’evna Levdanskaya (Наука. Инновации. Технологии)
Investigated the importance of innovative marketing tools to increase the efficiency of the territory of strategic marketing areas and the necessity of their application, the main directions of branding area on the example of the Stavropol Territory and The Republic Of Belarus